Multilocus and interaction-based genome scan for alcoholism risk factors in Caucasian Americans: the COGA study - Williams, Adrienne H (BioMed Central, 2005)
In this paper, we applied the nonparametric linkage regression approach to the Caucasian genome scan data from the Collaborative Study on the Genetics of Alcoholism to search for regions of the genome that exhibit evidence for linkage to putative alcoholism-predisposing genes. The multipoint single-locus model identified four regions of the genome with LOD scores greater than one. These regions were on 7p near D7S1790 (LOD = 1.31), two regions on 7q near D7S1870 (LOD = 1.15) and D7S1799 (LOD = 1.13) and 21q near D21S1440 and D21S1446 (LOD = 1.78). Jointly modeling these loci provided stronger evidence for linkage in each of these regions (LOD = 1.58 on 7q11, LOD = 1.61 on 11q23, and LOD = 1.95 on 21q22). The evidence for linkage tended to increase among pedigrees with earlier mean age of onset at 8q23 (p = 0.0016), 14q21 (p = 0.0079), and 18p12 (p = 0.0021) and with later mean age of onset at 4q35 (p = 0.0067) and 9p22 (p = 0.0008).